Governance and Firm Value: Audit Committee and Ownership as Moderators - Sunaryo, Dede; Febrianto, Hendra Galuh; Erdawati, Lena; Fitriana, Amalia Indah; Kartaloğlu, Mikail (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
Amid rising investor scrutiny and ESG-driven valuation pressures, the governance quality of consumer goods firms in emerging markets remains inconsistent. This study investigates how transparency, board independence, institutional Ownership, and audit committee effectiveness influence firm value, addressing the urgent need for integrated governance strategies in Indonesia’s Primary Consumer Goods sector. Using panel data from 2020 to 2024 and a fixed-effects regression model, the study tests the direct and moderating effects of governance variables. Results confirm that transparency and board independence significantly enhance firm value, while institutional ownership and audit committee effectiveness not only exert direct influence but also strengthen governance-performance linkages through interaction effects. The study contributes to governance literature by validating the layered nature of internal and external mechanisms and introducing a dual moderation framework. Its novelty lies in empirically demonstrating how governance synergies, rather than isolated mechanisms, drive valuation outcomes. Practically, the findings urge firms to institutionalise governance audits, attract strategic investors, and reinforce board-audit alignment. The study offers actionable insights for regulators, investors, and boards seeking to optimise governance for sustainable value creation.